2013
DOI: 10.1186/1471-2431-13-32
|View full text |Cite
|
Sign up to set email alerts
|

The intensity of physical activity influences bone mineral accrual in childhood: the childhood health, activity and motor performance school (the CHAMPS) study, Denmark

Abstract: BackgroundStudies indicate genetic and lifestyle factors can contribute to optimal bone development. In particular, the intensity level of physical activity may have an impact on bone health. This study aims to assess the relationship between physical activity at different intensities and Bone Mineral Content (BMC), Bone Mineral Density (BMD) and Bone Area (BA) accretion.MethodsThis longitudinal study is a part of The CHAMPS study-DK. Whole-body DXA scans were performed at baseline and after two years follows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 31 publications
1
40
0
1
Order By: Relevance
“…Until now, the most of study were focused on BMD of elite players in side-to-side effects, but a few investigations have been performed for normal people [30,31]. In this study, we observed that the non-dominant hand BMD of moderate and low physical activity groups were significantly lower than those in dominant hand, but did not in high activity group.…”
Section: Bmd In the Forearmsupporting
confidence: 48%
“…Until now, the most of study were focused on BMD of elite players in side-to-side effects, but a few investigations have been performed for normal people [30,31]. In this study, we observed that the non-dominant hand BMD of moderate and low physical activity groups were significantly lower than those in dominant hand, but did not in high activity group.…”
Section: Bmd In the Forearmsupporting
confidence: 48%
“…Although questionnaires are relatively easy to administer and enable the involvement of many participants, they introduce the risk of recall bias [13]. To avoid recall bias, researchers have begun to use accelerometers when investigating associations between objective measures of PA and bone properties; however, studies have focused on children and adolescents [14,15]. Furthermore, the use of dual-energy X-ray absorptiometry (DXA) to measure aBMD in two dimensions may result in measurement errors [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Total PA explained 1%-2% of the variability in BMC (Janz et al 2006) Children who maintained high levels of PA over the 3-y period (≥50th percentile) accrued, on average, 14% more trochanteric BMC and 5% more whole-body BMC relative to peers maintaining low levels of PA (<50th percentile) (Janz et al 2006) 1 study found that spending a higher proportion of total PA in MPA-VPA relative to LPA was favourably associated with BMC, BMD, and bone area (Heidemann et al 2013 (1/1 studies; Tobias et al 2007); Hip BMC: favourable associations (2/2 studies; Janz et al 2001Janz et al , 2014a; Spine BMC: associations were favourable (2/3 studies; Janz et al 2001 and …”
Section: No Serious Imprecisionmentioning
confidence: 99%
“…One longitudinal study found that spending a higher proportion of total PA engaged in MPA and VPA relative to LPA was prospectively associated with higher BMC, bone mineral density (BMD), and bone area (Heidemann et al 2013). There were mixed (favourable and null) associations between VPA and spine or hip BMC (2/2 studies; Francis et al 2014;Janz et al 2014a).…”
Section: Bone Healthmentioning
confidence: 99%
See 1 more Smart Citation